2010
DOI: 10.1016/j.jpor.2009.11.003
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the surface deposition on anodized-hydrothermally treated commercially pure titanium after immersion in simulated body fluid

Abstract: The results indicate that the deposits formed on SA-treated c.p.Ti surfaces contained calcium phosphate. These deposits may be formed as a consequence of the topography and physicochemical properties of SA-treated c.p.Ti surfaces and may play a key role in osteoconduction during osseous wound healing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
16
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 25 publications
2
16
0
Order By: Relevance
“…Thus, numerous strategies focusing on the surface modification of Ti alloys have been employed to render them protection from both wear, corrosion and even tribocorrosion [3][4][5]. The strategies include physical vapour deposition [6], thermal spray [6,7], ion or laser nitriding [8][9][10], thermal oxidation [11,12], micro-arc oxidation [13][14][15], diffusion [16] and anodic oxidation treatments [17]. On the other hand, the antibacterial properties are also necessary for Ti implant RESEARCH when exposed to the living tissue [18].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, numerous strategies focusing on the surface modification of Ti alloys have been employed to render them protection from both wear, corrosion and even tribocorrosion [3][4][5]. The strategies include physical vapour deposition [6], thermal spray [6,7], ion or laser nitriding [8][9][10], thermal oxidation [11,12], micro-arc oxidation [13][14][15], diffusion [16] and anodic oxidation treatments [17]. On the other hand, the antibacterial properties are also necessary for Ti implant RESEARCH when exposed to the living tissue [18].…”
Section: Introductionmentioning
confidence: 99%
“…(42) claimed that anodization using Ishizawa and Zuhs' methods did not result in mineralized surfaces after SBF soaking for 14 days. Recently, (69) found that apatite formation on anodized titanium formed at 350 V in 0.01M beta-GP and 0.15M CA after 28 day soaking in SBF. However, (42) two-step method followed by soaking in SBF resulted in a new mineral phase after incubation of only 6 days in Vogel's SBF.…”
Section: Many Different Types Of Sbf Solutions Have Been Developed Tomentioning
confidence: 99%
“…Further cellular work with hydrothermal treatment in steam at 300ºC for 2 hours, as in Ishizawa's method, was carried out by Takebe and others (5,23,24,36,69,73,74) using 0.01M beta-GP and 0.15M CA as the electrolyte during anodization. Using murine spleen cells and human peripheral blood mononuclear cells, no influence was observed in terms of LPS-induced proliferation of lymphocytes or LPS-induced IL-1α production between the treated AOFCP, AOFCP plus hydrothermal treatment and the untreated titanium cultured for up to 66 hours (23).…”
Section: Anodization + Hydrothermal Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Among different Caps, HA [Ca 10 (PO 4 ) 6 (OH) 2 ] is widely used due to its osseous nature and suitability to strong bonding with host bone tissues . Different coating methods have been utilized such as plasma spraying, dip coating, hot isostatic pressing, ion beam‐assisted deposition, pulsed laser deposition, sol–gel technique and electrophoretic deposition (EPD) . Among of these methods, EPD has several benefits such as better control thickness and morphology of the coating, components with complex shapes are deposited uniform, higher deposition rate than other coating technics and cheap equipment required …”
Section: Introductionmentioning
confidence: 99%